Embracing Digital Technology in Implantology: From Current Practice to Future Potential - Eweis, Islam Abdelaziz Mohamed; Rakha, Rana; Badve, Sonali; Nimale, Archana; Chokshi, Rohan; Rodil, Monica Milagros Parra; Singh, Sandeep (International Journal of Dental Materials, 2026)
Digitalization has transformed the field of implantology, enabling clinicians to achieve higher precision, efficiency, and predictability across all phases of treatment. This review explores the key digital technologies currently applied in implant dentistry, including cone-beam computed tomography, intraoral scanners, computer-aided design/computer-aided manufacturing systems, static and dynamic guided surgery, and emerging applications of artificial intelligence. These innovations have optimized diagnosis, virtual treatment planning, and surgical execution, enabled minimally invasive procedures and enhanced patient outcomes. Additionally, digital workflows have streamlined prosthetic design and fabrication, reduced chairside time and improved communication between clinicians, laboratories, and patients. However, challenges such as high initial investment, steep learning curves, software interoperability issues, and data security concerns remain barriers to universal adoption. Future research should focus on integrating artificial intelligence with robotics, advancing 3D printing for fully customized implants, and developing cost-effective, open-source solutions to make digital implantology more accessible worldwide. By critically reviewing current evidence, this paper highlights how digitalization continues to shape the future of implant dentistry and emphasizes the need for ongoing training, research, and innovation.